Cannabis use and reduced risk of elevated fatty liver index in HIV-HCV co-infected patients: a longitudinal analysis (ANRS CO13 HEPAVIH). Issue 9 (2nd September 2021) - Barré, Tangui; Rojas Rojas, Teresa; Lacombe, Karine; Protopopescu, Camelia; Poizot-Martin, Isabelle; Nishimwe, Marie Libérée; Zucman, David; Esterle, Laure; Billaud, Eric; Aumaitre, Hugues; Bouchaud, Olivier; Rey, David; et al.
ABSTRACT: Background : Cannabis use and elevated fatty liver index (FLI≥ 60) (a biomarker of hepatic steatosis in the general population) have been identified as predictors of HCV-related and overall mortality, respectively, in HIV-HCV co-infected patients. However, the relationship between cannabis use and the risk of elevated FLI has never been explored. Methods : Using five-year follow-up data from 997 HIV-HCV co-infected patients (ANRS CO13 HEPAVIH cohort), we analyzed the relationship between cannabis use and FLI using mixed-effects multivariable logistic (outcome: elevated FLI yes/no) and linear (outcome: continuous FLI) regression models. Results : At the last follow-up visit, 27.4% of patients reported regular or daily cannabis use and 27.8% had elevated FLI. After multivariable adjustment, regular or daily cannabis use was associated with a 55% lower risk of elevated FLI (adjusted odds ratio [95% confidence interval]: 0.45 [0.22; 0.94]; p = 0.033) and lower FLI values (adjusted model coefficient: −4.24 [−6.57; −1.91], p < 0.0001). Conclusions : Cannabis use is associated with a reduced risk of elevated fatty liver index in HIV-HCV co-infected patients. Further research is needed to confirm whether and how cannabinoids may inhibit the development of hepatic steatosis or other metabolic disorders in high-risk populations.